2015
DOI: 10.1002/14651858.cd007079.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Calcium supplementation (other than for preventing or treating hypertension) for improving pregnancy and infant outcomes

Abstract: This review indicates that there are no clear additional benefits to calcium supplementation in prevention of preterm birth or low infant birthweight. While there was a statistically significant difference of 56 g identified in mean infant birthweight, there was significant heterogeneity identified, and the clinical significance of this difference is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 71 publications
1
39
0
1
Order By: Relevance
“…Systematic reviews of studies on the effect of maternal calcium supplementation on several pregnancy and infant outcomes concluded that calcium supplementation has no significant effect on infant length and HC but resulted in a small increase (65-80 g) in birth weight (30)(31)(32), supporting the hypothesis that calcium 2 P values refer to the comparison between the calcium plus vitamin D and placebo groups by using ANCOVA after adjusting for significant covariates. 3 Factors tested in the overall group by using multiple linear regression models for measurements at birth were ppBMI, dietary calcium intake during pregnancy, maternal supplementation may increase somatic fetal growth.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Systematic reviews of studies on the effect of maternal calcium supplementation on several pregnancy and infant outcomes concluded that calcium supplementation has no significant effect on infant length and HC but resulted in a small increase (65-80 g) in birth weight (30)(31)(32), supporting the hypothesis that calcium 2 P values refer to the comparison between the calcium plus vitamin D and placebo groups by using ANCOVA after adjusting for significant covariates. 3 Factors tested in the overall group by using multiple linear regression models for measurements at birth were ppBMI, dietary calcium intake during pregnancy, maternal supplementation may increase somatic fetal growth.…”
Section: Discussionmentioning
confidence: 95%
“…3 Factors tested in the overall group by using multiple linear regression models for measurements at birth were ppBMI, dietary calcium intake during pregnancy, maternal supplementation may increase somatic fetal growth. However, the clinical significance of this small effect on birth weight was considered uncertain (30,31). In fact, no effect on infant birth weight, length, and HC were observed in randomized controlled maternal calcium supplementation trials in different populations (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one reviews reported on LBW, 24-44 11 on SGA 29 31-33 35-39 45 46 and 3 reviews on IUGR. 28 45 46 Two studies reported VLBW 30 32 while none of the included reviews reported ELBW. Twenty-two studies assessed the effect of the interventions on PTB.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…30 The number of included participants in the reviews ranged from 603 participants 41 to over 310 000 participants. 24 Supplementation with vitamins was reported in five reviews, 24-26 45 46 supplementation with minerals in eight reviews [27][28][29][30][31][32][33][34] and MMN supplementation was assessed in three reviews. [35][36][37] There was one review on protein supplementation and nutritional education 38 and two reviews reported on marine oil and fatty acid supplementation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation